(untitled) (Fiep Bulletin - online, 2014)
Between 1960 and 1980 there was a 33% fall in fecundity in Brazil. This brings as a result, in a medium range, a growth in the elderly population and also a decrease of physical capacities related to the performance of everyday tasks. The objective of this study was to evaluate the boy composition, fall incidence during12 months and the myoelectrical activity of the muscles rectus femoris and vastus medialis, tibialis anterior and gastrocnemis of 34 sedentary subjects, mean age 69,3 ± 7,3 and 40 subjects that exercised 3 times per week, an hour a day, mean age 71,5 ± 5,6. The Body Mass Index (BMI) was used to evaluate the body composition. A questionnaire was applied to determine the fall incidence during 12 months and an eight-channel electromyograph produced by EMG SYSTEM do Brasil was used to determine the muscles electrical activity. Results show that exercised individuals are less subject to overweight and obesity (66% vs 82%) falls (19% vs 60%) than those belonging to the sedentary group. Furthermore, the exercised group presented more electrical activity in all the muscles studied (rectus femoris 38,1v vs 28,3v; vastus medialis 42,8v vs 28,2v; tibialis anterior 81,5v vs 57,2v and gastrocnemis 112,7v vs 52,6v). Results also suggest that an active lifestyle minimizes the neuromotor system deterioration, reducing the motor unit loss and physical capacities, which leads to less falls and to the preservation of older adults’ autonomy.